2020
DOI: 10.3390/ani10010150
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Beef Tenderloin and Flank Assessed Using an Isobaric Tag for Relative and Absolute Quantitation (iTRAQ)

Abstract: Herein, we performed a proteomic analysis of tenderloin and flank steaks from Simmental cattle using the isobaric tags for a relative and absolute quantification (iTRAQ) approach. We identified 17 amino acids in both steaks, and Gly, Cys, Ile, Lys, and Pro differed most in abundance between the steak types (p < 0.05). A comparison of the expression patterns in steaks revealed 128 differentially expressed proteins (DEPs), of which 44 were up-regulated and 84 were down-regulated. Furthermore, 27 DEPs (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Oxidative phosphorylation is a pathway that uses energy released from the oxidation of nutrients to produce ATP [61]. A recent study showed the downregulation of differentially expressed proteins associated with oxidative phosphorylation, indicating a high level of energy metabolism in muscle [62]. The TGF-beta signaling pathway is involved in cell proliferation, differentiation, and signal transduction [63].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative phosphorylation is a pathway that uses energy released from the oxidation of nutrients to produce ATP [61]. A recent study showed the downregulation of differentially expressed proteins associated with oxidative phosphorylation, indicating a high level of energy metabolism in muscle [62]. The TGF-beta signaling pathway is involved in cell proliferation, differentiation, and signal transduction [63].…”
Section: Discussionmentioning
confidence: 99%
“…The e cient utilization of energy in Tibetan pigs was also helpful for subsequent research on the meat quality, and speculating the changes in energy reserves and metabolism in human body after eating Tibetan pork. Furthermore, proteomics studies of other meats have found that differentially expressed proteins from grouper llets were mainly involved in carbon metabolism and microbial metabolism in diverse environments [44], most of the differentially expressed proteins of beef tenderloin and ank steaks were related to amino acid and energy metabolism [45], and the differentially expressed proteins of chicken skeletal muscle were mainly involved in ribosome and muscle contraction pathways [46]. Tibetan pork's proteomics research results are different from other types of meats, its advantages are worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, proteomics analysis based on the ‘isobaric tag’ for relative and absolute quantitation (iTRAQ) technology has been widely applied to the research of meat quality (Lei et al ., 2020). The iTRAQ technology exhibits high efficiency, which can enormously reduce the sample processing and experimental errors caused by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…The iTRAQ technology exhibits high efficiency, which can enormously reduce the sample processing and experimental errors caused by different groups. It can systematically study as many proteins as possible in the organization, and detect protein present at both low and high levels (Shi et al ., 2018; Lei et al ., 2020). Phosphorylation proteomics is based on the enrichment and purification of phosphorylated peptides, with the difference of phosphorylated proteins analyzed by mass spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%